Bioequivalence of a New Oral Levosulpiride Formulation Compared With a Standard One in Healthy Volunteers. Issue 2 (April 2017) - De Gregori, Simona; Cipollina, Laura; De Silvestri, Annalisa; Ventura, Marianna; Michelini, Roberta; Morosini, Monica; Montagna, Michela; Tinelli, Carmine; Regazzi, Mario; Molinaro, Mariadelfina; Imberti, Roberto
Abstract : Background: A monocentric, single-dose, open-label, 2-way, crossover randomized study was conducted by the San Matteo Phase I Clinical Trial Unit and Experimental Therapy (Pavia, Italy) to assess the bioequivalence and the systemic tolerability of a new oral formulation of levosulpiride (tablet 25 mg: test) versus a commercially available formulation on the Italian market (tablet 25 mg: reference). Methods: Thirty-five healthy adult volunteers, men (n = 19) and women (n = 16), aged between 18 and 55 years were screened and 32 of them were enrolled in the study. After having signed the written informed consent, each subject received a single oral dose of Test or Reference product with 250 mL of natural mineral water, in fasting conditions, interspersed with a 6-day washout period Blood samples were collected up to 36 hours after drug administration: the drug plasma levels were determined by high-performance liquid chromatography coupled with electrospray ionization tandem mass spectrometry. The pharmacokinetic parameters included peak plasma concentration (Cmax ), time corresponding to Cmax (tmax ), area under the plasma concentration–time curve from zero to infinity (AUC0 –∞ ) or to the last sampling time assessment (AUC0–36 ), the elimination rate constant (ke), and the terminal half-life (t1/2 ). Safety was measured by pre- and post-treatment specific biochemical investigations, physical examination, electrocardiogram, occurrence of adverse events, and any information on patients' withdrawal. Results: The geometric mean ratio Test/Reference (90% confidence interval) for levosulpiride was 103.0% (95.8–110.8) for AUC0–36, 103.6% (95.9–111.9) for AUC0–∞, and 104.3% (94.9–114.6) for Cmax . ke and t1/2 were 0.07 (SD: 0.02) and 9 hours (8–12) for both the formulations. Clearance (L/h) was 29.6 (±13.5) and 30.7 (±14.2) for the test and the reference product, respectively. Conclusions: Because the acceptance criteria required by the drug regulatory agency (European Medicines Agency, EMA) for bioequivalence prescribe limits of 80%–120% for untransformed data and 80%–125% for " ln " transformed data, we can confirm that the 2 formulations are bioequivalent, in terms of the rate and extent of absorption.